Terjemahan Gaya dalam Teks Pidato Presiden Jokowi dari Bahasa Indonesia ke dalam Bahasa Mandarin - Hutabarat, Adinda N.V. (Kementerian Sekretariat Negara Republik Indonesia, 2021)
This research focused on the use of style translation method in Mandarin news media in Indonesia. The research on parts of the five political speeches of the President of Republic of Indonesia (Jokowi) throughout his first administrative period (2014-2019), and one political speech’ parts that were published in four online news media from bahasa Indonesia as the Source Texts (ST) into Mandarin as the Target Texts (TT) in Mandarin news media in Indonesia. It is aiming at showing that a ST’s message is conveyed accurately or inaccurately in the TT through style translation. This research uses descriptive qualitative method in collecting and analyzing its data, namely comparative model of the ST and TT. In order to reveal the style translation, the analysis in particular is according to the categorization of “powerful style in Mandarin”. This research reveals that Jokowi’s speech texts frequently use styles, in successive which are (i) repetition, (ii) parallelism, (iii) rhyming in sizizuhe/Proverb, and (iv) rhetorical question. Keywords: Translation, Style, Speech, Jokowi, bahasa Indonesia-bahasa Mandarin.